(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
The present study aims to unfold the post-modernistic concept of Falsification of Identity in the selected novels of Abdulrazak Gurnah. The concept of Falsification of identity is a false representation of identity, culture, religion, and name of someone or something for particular purposes. Moreover, the concept also refers to a person who adopts a false identity or someone else's identity to get benefits or hide problematic relationships with the state, society, and so on. In the Postmodern era, there are new ideas, generative meaning, competitiveness, and opportunities increased to benefit individual imitates the things surrounding them. His imitations of things help him to create a camouflage around to not be easily identified by others. Published in 2001, the story of the novel By the Sea is about Saleh Omar. Saleh Omar belongs to Zanzibar society. He was exiled from England to escape persecution after being falsely implicated through deceit and betrayal. In his quest for safety, Omar gets an alternate identity or fake identity and adopts the name “Rajab Shaaban Mahmud” for his counterfeit passport. As a result, he gets a citizenship of another country. Another integral part of the novel revolves around Latif Mahmud, the son of the real Rajab Shaaban Mahmud. Latif pursues a legitimate path to Europe, acquiring a student visa for East Germany and embarking on a circuitous journey to the UK. However, his purpose takes a different direction than his father's, as he seeks to vindicate his own losses and come to terms with the complexities of his heritage.